2023
DOI: 10.3390/ani13060999
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Chronic Progressive Lymphedema in the Rhenish German Draught Horse

Abstract: Chronic progressive lymphedema (CPL) is a common disease in Rhenisch German draught horses. The objective of our study was to evaluate the prevalence of this disease and its progression with age in 493 Rhenish German draught horses from different regions in Germany. We employed generalized linear models with binomial, multinomial, and normal distributions to analyse the effects of breeding association, coat colour, sex and age within sex, time of examination, limb on which CPL was recorded, and farm-related fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(28 citation statements)
references
References 21 publications
(112 reference statements)
0
12
0
Order By: Relevance
“…The severity of lesions, especially the skinfold thickness, increases for both mares and stallions from the age of 3 years onwards [ 9 ]. Sievers and Distl also confirmed that the first onset of clinical signs starts in horses aged 1–2 years [ 62 ]. The disease progression ceases at a mean age of 16 years in stallions, 18 years in geldings, and 20 years in mares [ 62 ].…”
Section: Factors Associated With Occurrence and Severity Of Cplmentioning
confidence: 86%
See 4 more Smart Citations
“…The severity of lesions, especially the skinfold thickness, increases for both mares and stallions from the age of 3 years onwards [ 9 ]. Sievers and Distl also confirmed that the first onset of clinical signs starts in horses aged 1–2 years [ 62 ]. The disease progression ceases at a mean age of 16 years in stallions, 18 years in geldings, and 20 years in mares [ 62 ].…”
Section: Factors Associated With Occurrence and Severity Of Cplmentioning
confidence: 86%
“…Sievers and Distl also confirmed that the first onset of clinical signs starts in horses aged 1–2 years [ 62 ]. The disease progression ceases at a mean age of 16 years in stallions, 18 years in geldings, and 20 years in mares [ 62 ].…”
Section: Factors Associated With Occurrence and Severity Of Cplmentioning
confidence: 86%
See 3 more Smart Citations